Call for Papers: IJPS volume 12, issue 1 - Stephanie Gingerich; Stephanie Doscher (Interdisciplinary Journal of Partnership Studies)
The importance of interdisciplinary partnerships to address interconnected local and global challenges has never been more pressing. The Interdisciplinary Journal of Partnership Studies (IJPS) invites scholars, practitioners, and thought leaders from all disciplines to submit original articles for our first issue in 2025.